2010
DOI: 10.1097/mnm.0b013e3283384587
|View full text |Cite
|
Sign up to set email alerts
|

Role of [18F]FDG-PET/CT in the detection of occult recurrent medullary thyroid cancer

Abstract: [(18)F]FDG-PET/CT seems to be valuable for the detection of recurrence in patients with highly elevated calcitonin levels and negative conventional imaging findings. In addition, it seems that the sensitivity of [(18)F]FDG-PET/CT may be higher in patients with sporadic or familial MTC than in patients with MTC as part of multiple endocrine neoplasia type IIA syndrome.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
53
1

Year Published

2011
2011
2017
2017

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(56 citation statements)
references
References 19 publications
2
53
1
Order By: Relevance
“…A possible explanation for this low 18 F-FDG PET/CT sensitivity (17%) in our series when compared to those reported in the literature (30-95%) could be related to the significant number of MTC [8,9,11,[13][14][15][23][24][25][26][27][28][29][30][31][32][33]. Nevertheless, 18 F-FDG PET/CT may provide useful information in patients with more aggressive disease, as demonstrated in patient 4 in whom it detected multiple liver lesions that were missed on functional PET/CT with the other two tracers, as well as two additional locoregional lymph nodes.…”
Section: Discussioncontrasting
confidence: 49%
“…A possible explanation for this low 18 F-FDG PET/CT sensitivity (17%) in our series when compared to those reported in the literature (30-95%) could be related to the significant number of MTC [8,9,11,[13][14][15][23][24][25][26][27][28][29][30][31][32][33]. Nevertheless, 18 F-FDG PET/CT may provide useful information in patients with more aggressive disease, as demonstrated in patient 4 in whom it detected multiple liver lesions that were missed on functional PET/CT with the other two tracers, as well as two additional locoregional lymph nodes.…”
Section: Discussioncontrasting
confidence: 49%
“…However, given the heterogeneity of MTC phenotypic expression, 18 F-FDG PET may be best suited to detect only a small subset of biologically aggressive tumors that overexpress glucose transporter proteins [18]. Other novel non-18 F-FDG positron-emitting radiopharmaceuticals such as 18 F-fluorodihydroxyphenylalanine ( 18 F-DOPA) and 68 Ga-1,4,7,10-tetraazacyclododecane-1,4,7,10-tetraacetic acid (DOTA) somatostatin analogues have been used to successfully image a wide variety of NETs, including MTC, and several studies have demonstrated superior sensitivity compared with 18 F-FDG PET for detection of MTC.…”
Section: Introductionmentioning
confidence: 99%
“…The follow up of these patients is more difficult, since serum calcitonin is of no use. Most authors suggest a neck ultra sound, an x-ray or CT of the thorax, an ultra sound or MRI of the liver, and measurements of serum calcitonin and CEA [10,15] , upon follow up, and if needed [18F] FDG-PET/CT [15,17]. Of course if a RET mutation is discovered the follow up must include evaluation of PTH and catecholamines/ metanephrines.…”
Section: Discussionmentioning
confidence: 99%